Capra, Postmodern Response and Ecological Paradigm - Morales, Gerardo (2005)
The ‘ecological paradigm’ posed by the Austrian physicist Fritjof Capra is summarized and explained. Paradigm which interrelates the perspective of the complex systems of the disciplines that study the life  processes  with  those  that  study  social  and cultural action. This perspective, seen as a revision of the mechanistic paradigm and of enlightended reason, is related with the postmodern contestation climate which demands a new instrumental and substantial rationality. Finally, some topics of the ecological paradigm are documented.